The Art Museum Propelling City Development – Oslo as a Creative City - Henrichsen, Stein Olav (Journal of Urban Culture Research, 2014)
A new boost in art infrastructure in the Norwegian capital Oslo will have a great impact on contemporary city development, and the important question is how this impact can be used to help build a sound society where democracy, human rights and financial development can prosper, and where conflicts can be discussed and solved in a non violent order. The answer depends on the ability of the institutions to play a relevant part in contemporary core problems and ask: what are societies main challenges, and how can we help solve them? In the further development of art institutions, they will have to strengthen their role as an attractive, accessible and vibrant part of society by inspiring creative and constructive critique in addition to their traditional tasks. Art institutions will have to bring important contemporary issues such as human rights and dignity, migration, poverty and crime up for reflection and discussion. By investigating and act on the human condition, peoples lives and society development art institutions can and should make an important difference.